Knowledge Management using Ontology Based Tantra Framework for Good Governance - Prabhu, Shreekanth M.; Balasubramanya Murthy, K. N.; Natarajan, S. (Journal of Information and Knowledge, 2018)
This paper proposes ontology-based Tantra Framework that accommodates Societal Information in an orderly, compact and unified manner to achieve Good Governance. In this work, Zachman Framework for Enterprise Architecture is used as reference and it is extended to address information operating at societal scale. The complexity of social information gets accentuated due to myriad possibilities of relationships, say compared to information pertaining to an Enterprise. In light of that, two additional columns namely relationships and relators have been added to Zachman Framework in Tantra Framework. The existing six columns of Zachman Framework namely who, what, how, when, where and why are interpreted as People, Assets/Attributes, Process, Event, Location and Objectives respectively. In addition to the six interrogatives of Zachman Framework that are ontology based, the concept of relationships and relators has been derived from The Unified Foundational Ontology. Even though Zachman considered his framework as Ontology, some researchers regarded it as taxonomy. Tantra Framework has addressed that perceived gap by extending the Zachman Framework by adding two additional columns. Application ScenariosThe utility of Tantra Framework is analyzed by applying it to a set of Application Scenarios pertaining to People and Locations information, Revenue Capture, Social Benefit Coverage Analysis, Financial Inclusion and Metrics analysis. Tanta Framework interoperates with Balanced Score Card approach to set objectives, Theory of Change to lay out a process of change and Bartels’ theory of Market Separations to assess the access barriers within Society. This research study is focused on Indian context. Tantra Framework relies on eliciting the inherent order in social information to make it complete, correct and current. For example, in Chemistry, discovery of periodic table by Mendeleev led to a unifying scheme which not only captured the present but allowed for place-holders for future discoveries. A similar focus on eliciting inherent order in social information, can potentially reveal latent ‘facts’, ‘truths’ and ‘relationships.